The FEL in the SXL project at MAX IV. (2nd May 2021) - Qin, Weilun; Curbis, Francesca; Andersson, Joel; Goryashko, Vitaliy; Isaksson, Lennart; Kyle, Billy; Lindau, Filip; Mansten, Erik; Pop, Mihai; Salén, Peter; Tarawneh, Hamed; Tavares, Pedro F.; et al.
Abstract : The design of a soft X‐ray free‐electron laser for the SXL project at the MAX IV Laboratory is presented. Abstract : In this paper the design of the free‐electron laser (FEL) in the SXL (Soft X‐ray Laser) project at the MAX IV Laboratory is presented. The target performance parameters originate in a science case put forward by Swedish users and the SXL FEL is foreseen to be driven by the existing MAX IV 3 GeV linac. The SXL project is planned to be realized in different stages and in this paper the focus is on Phase 1, where the basic operation mode for the FEL will be SASE (self‐amplified spontaneous emission), with an emphasis on short pulses. Simulation results for two linac bunches (high and low charge) with different pulse duration are illustrated, as well as the performance for two‐color/two‐pulses mode and power enhancement through tapering. Besides standard SASE and optical klystron configurations, the FEL setup is also tailored to allow for advanced seeding schemes operations. Finally possible upgrades that will be implemented in a second phase of the project are discussed.